Contributions of left frontal and temporal cortex to sentence comprehension: Evidence from simultaneous TMS-EEG. (June 2019) - Kroczek, Leon O.H.; Gunter, Thomas C.; Rysop, Anna U.; Friederici, Angela D.; Hartwigsen, Gesa
Abstract: Sentence comprehension requires the rapid analysis of semantic and syntactic information. These processes are supported by a left hemispheric dominant fronto-temporal network, including left posterior inferior frontal gyrus (pIFG) and posterior superior temporal gyrus/sulcus (pSTG/STS). Previous electroencephalography (EEG) studies have associated semantic expectancy within a sentence with a modulation of the N400 and syntactic gender violations with increases in the LAN and P600. Here, we combined focal perturbations of neural activity by means of short bursts of transcranial magnetic stimulation (TMS) with simultaneous EEG recordings to probe the functional relevance of pIFG and pSTG/STS for sentence comprehension. We applied 10 Hz TMS bursts of three pulses at verb onset during auditory presentation of short sentences. Verb-based semantic expectancy and article-based syntactic gender requirement were manipulated for the sentence final noun. We did not find any TMS effect at the noun. However, TMS had a short-lasting impact at the mid-sentence verb that differed for the two stimulation sites. Specifically, TMS over pIFG elicited a frontal positivity in the first 200 msec post verb onset whereas TMS over pSTG/STS was limited to a parietal negativity at 200–400 msec post verb onset. This indicates that during verb processing in sentential context, frontal brain areas play an earlier role than temporal areas in predicting the upcoming noun. The short-living perturbation effects at the mid-sentence verb suggest a high degree of online compensation within the language system since the sentence final noun processing was unaffected.